Extension of the TOPSIS method to group decision-making - ZARE, Sougoursi Jean Yves; SAVADOGO, Zoïnabo; ZONGO, Wambie; SAWADOGO, Somdouda; SOME, Blaise (International Journal of Applied Mathematical Research, 2022)
TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) is a very practical decision support method used in several areas of life. This method already exists in the literature in the context of a single decision maker. In order to adapt this method to group decision making, which can be easily applied in various situations, this work extended the TOPSIS method to group decision making using the quadratic mean and the geometric mean. In this work, numerical applications have been made and interesting results have been obtained.